Engineering highly efficient Eu(III)-based tri-ureasil hybrids toward luminescent solar concentrators - Nolasco, Mariela M.
Following a computational-experimental approach, a highly luminescent beta-diketonate-europium(III) complex containing 2-thenoyltrifluoracetonate (tta(-)) and 5,6-epoxy-5,6-dihydro-[1,10] phenanthroline (ephen) ligands, Eu(tta)(3)ephen (II), was theoretically studied by DFT/TD-DFT calculations, synthesized from Eu(tta)(3)(H2O)(2)(I) and fully characterized by high resolution mass spectrometry, TGA analysis, vibrational, UV-Vis and photoluminescence spectroscopy. For intramolecular energy transfer analysis purpose, Ln(NO3)(3)(ephen)(2) [Ln = Eu (III), Gd (IV)] complexes were also synthesized and complexes I and III were theoretically studied. The organic-inorganic tri-ureasil matrix was used as a support for the immobilization of complex II and two hybrid samples were synthesized as a monolith (MtU5Eu-II) and as a thin film (FtU5Eu-II), characterized and its photoluminescence properties were compared with those of complex II. The photophysical properties of complex II benefit from the synergy between the excited-states of both ligands that create efficient energy transfer pathways to optimize the Eu3+ sensitization contributing to the large emission quantum yield (82 +/- 8%), which is one of the highest so far reported for solid lanthanide beta-diketonate complexes. Moreover, although the incorporation of complex II into the hybrid matrix is disadvantageous from the quantum yield point of view, MtU5Eu-II and FtU5Eu-II exhibit the highest emission quantum yields reported so far for Eu3+-containing hybrids (63 +/- 6% and 48 +/- 5%, respectively). Additionally, a significant improvement in the photostability under UV irradiation of the incorporated complex II is observed. The possibility of FtU5Eu-II to be used as a luminescent solar concentrator was evaluated and an optical conversion efficiency of similar to 9% as well as an ability to boost up the Si-photovoltaic cell output to 0.5% were verified.